CONTRIBUTION OF TUROR RISKULOV TO THE CAUSE OF NATIONAL STATE BUILDING IN TURKESTAN (Scientific journal of the Fergana State University, 2024)
The article analyzes the participation of Turor Riskulov in the formation of the political position and economic image of new state structures that arose as a result of the total collapse of the economy of the Russian Empire, especially in the first years after the October Revolution. In modern conditions, it is very important to evaluate the contribution of the Turkestan state and scientists to the economy and socio-political development of society. The article also reveals state borders, collectivization and five-year plans, which radically changed the socio-economic system, as well as the development of the economy and the standard of living of the poorest segments of the population, as well as the reverse, negative sides.